Harnessing local arts through android technology to boost critical reading among students - Fujiastuti, Ariesty; Himawan, Riswanda; Wirawati, Denik; Sularso, Sularso (Psychology, Evaluation, and Technology in Educational Research, 2024)
The purpose of this research is to develop android-based reading learning media and local culture for students. The method used is Research and Development (R&D) with the ADDIE model. The results of the study showed the less than-optimal use of devices in learning to read. Product design involves designing the interface and teaching materials. Product development includes implementation of the initial design, validation by material and media experts, and evaluation of student responses. The feasibility test results showed good and very good categories from material and media experts, as well as positive student responses. The product effectiveness test showed an increase in student learning outcomes in the reading course. Evaluation was conducted to reflect on the development results and develop other products relevant to learning.